67+c=-789

Simple and best practice solution for 67+c=-789 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 67+c=-789 equation:


67+c=-789

We simplify the equation to the form, which is simple to understand
67+c=-789

We move all terms containing c to the left and all other terms to the right.
+1c=-789-67

We simplify left and right side of the equation.
+1c=-856

We divide both sides of the equation by 1 to get c.
c=-856

See similar equations:

| -4.6=3.4-2y | | (a+9)+7bi=9-6i | | 7Y+10=3Y-2 | | 1-x=15-3x | | 5y+4x=2 | | 3x+2x+x+12+2x/4=360 | | 27=v+15 | | 5v-4=-4v+8v | | -6.7-6X=-0.1 | | 12+x=4+2x | | 5x+40f(x)x=-5 | | 6x^2=12x-9 | | Cos(4x-10)=0 | | 7x-5y=-68 | | H=-5t^2+7t-4 | | 1x+4y=120 | | 1x+4y=11120 | | 2-2v=v+64 | | x-11=90 | | 3x+y-z=1 | | 0.9375=x+0.25(3) | | 6x-2y-z=-14 | | f(x)=13x+52 | | 2lgx=2 | | (n+5)(p-14)=1400 | | 6y+2z=a+3y | | 2x+3y+z=1 | | 6y+2z=a+3fory | | 0=-5x^3+25x^3-17x | | 4x+3y=330 | | 10-5x=3x+6 | | -3(4p+4)-2(6-11p)=3(8+3p) |

Equations solver categories